Melt Blends of Poly(lactic acid)/Natural Rubber and Liquid Epoxidised Natural Rubber - Mohd Bijarimi, Mat Piah; Sahrim, Ahmad; Rozaidi, Rasid (Malaysian Rubber Board, 2014)
Although poly(lactic acid) (PLA) is among widely used biodegradable polymers, it has limited applications due to its inherent brittleness, low elongation at break and toughness. Blending with natural rubber (NR) and epoxidised natural rubber (ENR) seems to be a promising alternative, as both materials are derived from renewable resources. Natural rubber was melt-blended with poly(lactic acid) in an internal mixer, Haake Rheomix, with a rotor speed of 50 r.p.m. at 180ºC. Liquid epoxidised natural rubber (LENR) was used as a compatibiliser in the binary blending system of thermoplastic natural rubber (TPNR). Results indicate that the mixing torque value and stabilisation torque value in LENR blends are lower than in blends without the compatibiliser. Various compositions of natural rubber, epoxidised natural rubber and compatibiliser were investigated with respect to the stress-strain behaviour. It was found that the addition of LENR compatibiliser improved the stress at break and Young’s modulus in the blend system of 40/60 PLA/rubber compositions. The increase in stress at break and Young’s modulus were associated with the ability of LENR to compatibilise the PLA/NR binary blends.